Historical influences to present legal setting of planning law in Malaysia - Ahmad Sarkawi, Azila; Abdullah, Muhammad Faris (Malaysian Institute of Planners, 2014)
Malaysia is a federation of thirteen states and three federal territories. Thus, it is a challenge to achieve uniformity of laws among the states. Presently, there are four sets of planning laws applicable in Malaysia. This paper looks at the historical factors that led to the non-uniformity of planning law in Malaysia. By using historical research methodology, this study found that the emergence of individual states back in the year 1400 AD is among the historical factors contributing to this non-uniformity of law. Additionally, the colonisation and the British influence over Malay Peninsula and the Borneo region, the formation of the Malaya Federation and the creation of federal territories also have strong implications in terms of administration and law uniformity. Despite the states eventually united under the essence of federation in 1963, this did not entail uniformity of laws among them. Additionally, states also have no obligation to adopt laws enacted by the Federal Government. Nevertheless, efforts to harmonise planning in the country have been undertaken. These include the amendment of planning laws and the establishment of national level planning committee.